Pengaruh Motivasi Dan Lingkungan Terhadap Minat Berwirausaha ( Studi Pada Marketplace Facebook Kota Kupang ) - Limbak, Angga Anggraini; Nursiani, Ni Putu; Fanggidae, Rolland E. (LPPM STIE KRAKATAU, 2023)
The new features launched by Facebook have made many entrepreneurs take advantage of the Facebook marketplace to promote their products to consumers. Although the Facebook marketplace is relatively new compared to other marketplaces, Facebook itself is familiar in various circles of society, especially in its use, Facebook is very easy to use so that users quickly understand access. This study aims to determine the effect of motivation and environment on entrepreneurial interest both partially and simultaneously. The method in this study uses descriptive quantitative research and quantitative research approach using data collection techniques in the form of questionnaires, observation and documentation. in addition, the population of this study are entrepreneurs in the Facebook Marketplace Kupang City which can not be known the exact number so that the sample withdrawal is done using random sampling with lemeshow formula obtained 96 samples. The analysis technique in this study uses multiple linear regression using SPSS version 21 data. Hypothesis testing is done with the t test and the F test where before using this test the classical assumption test is performed. Partial test results show that the motivation variable has a positive and significant effect on entrepreneurial interest, environmental variables have a positive and significant effect on entrepreneurial interest. Simultaneous test results show that the variables of motivation and environment simultaneously affect the interest in entrepreneurship.